A 2D and 3D X-ray μ-diffraction and μ-fluorescence study of a mixed ionic electronic conductor. (12th January 2017) - Sanchez, Dario Ferreira; Grolimund, Daniel; Hubert, Maxime; Bleuet, Pierre; Laurencin, Jérôme
Abstract: Due to the mixed ionic electronic conductive properties of the Lanthanum Strontium Cobalt Ferrite (LSCF) La0.6 Sr0.4 Co0.2 Fe0.8 O3−δ compound, it is of great scientific and technological interest. Especially in the Solid Oxide Fuel Cell (SOFC) technology, this compound has receiving great attention as a cathode material. However, its chemical reactivity with the Yttria-stabilized Zirconia (YSZ) electrolyte still remains one of the main challenges, which demands a comprehension in the μm and sub-μm range. In order to address the reactivity issues locally in the micrometre scale range, 2D and 3D X-ray μ-diffraction and μ-fluorescence analysis have been performed on a pristine LSCF cathode layer. The cathode was deposited on a dense YSZ electrolyte substrate spaced by a thin Gadolinium doped Ceria Oxide (CGO) barrier layer in between LSCF and YSZ to limit the reactivity. The present approach offers a larger field of view in comparison to electron microscopy techniques. The method can provide a more representative information and may offer some insights on the reactivity distribution along the interfaces. The formation of micro SrZrO3 inclusions in LSCF layer is then indubitably identified, as well as in the CGO/YSZ interface. Graphical abstract: Highlights: A 2D and 3D-tomography X-ray μ-diffraction and μ-fluorescence study is performed. Pristine LSCF, spaced by thin CGO layer from a dense 8YSZ electrolyte is studied. The formation of micro SrZrO3 inclusions in 23 μm thick LSCF layer is identified. The formation of the SrZrO3 is also identified in the CGO/YSZ interface region. Tetragonal YSZ phase possibly been formed also in the CGO/YSZ interface region.